Modulation of EEG theta band signal complexity by music therapy - Bhattacharya, Joydeep; Lee, Eun-Jeong (International journal of bifurcation and chaos (IJBC), 2016)
The primary goal of this study was to investigate the impact of monochord (MC) sounds, a type of archaic sounds used in music therapy, on the neural complexity of EEG signals obtained from patients undergoing chemotherapy. The secondary goal was to compare the EEG signal complexity values for monochords with those for progressive muscle relaxation (PMR), an alternative therapy for relaxation. Forty cancer patients were randomly allocated to one of the two relaxation groups, MC and PMR, over a period of six months; continuous EEG signals were recorded during the first and last sessions. EEG signals were analyzed by applying signal mode complexity, a measure of complexity of neuronal oscillations. Across sessions, both groups showed a modulation of complexity of beta-2 band (20-29<mspace width=".17em"></mspace>Hz) at midfrontal regions, but only MC group showed a modulation of complexity of theta band (3.5-7.5<mspace width=".17em"></mspace>Hz) at posterior regions. Therefore, the neuronal complexity patterns showed different changes in EEG frequency band specific complexity resulting in two different types of interventions. Moreover, the different neural responses to listening to monochords and PMR were observed after regular relaxation interventions over a short time span.
Gesehen am 11.05.2020